A novel rat model of incisional surgical site infection model developed using absorbable multifilament thread inoculated with Escherichia coli. Issue 4 (April 2015) - Fujimura, Naoki; Obara, Hideaki; Suda, Koichi; Takeuchi, Hiroya; Matsuda, Sachiko; Kurosawa, Tomoko; Katono, Yasuhiro; Murata, Mitsuru; Kishi, Kazuo; Kitagawa, Yuko
Abstract: The development of an effective rat model of incisional surgical site infection (SSI) has so far proven difficult. In this study, we created a novel incisional SSI model and validated it in terms of both macroscopic and microscopic aspects including its response to treatment using antimicrobial wound-dressing, Aquacel Ag ® . Wounds were created on the dorsum of rats. 3-0 Vicryl ®  threads inoculated with Escherichia coli were inserted in the wound beds in the infection group ( n  = 6). The wounds were closed for two days to induce infection and then opened and covered with polypropylene sheets during the study. Aquacel Ag was placed under the polypropylene sheet in the infected wounds of the Aquacel Ag group rats ( n  = 6). The wounds in the control group ( n  = 6) contained sterile Vicryl thread that had not been inoculated with E . coli . The macroscopic appearance, wound area, bacterial counts, and histology of each group were evaluated. The infection group demonstrated significantly lower wound healing ( p  < 0.001), greater bacterial counts (median [interquartile range] ratings, 2.15 × 10 7 [0.51 × 10 7 –53.40 × 10 7 ] vs 2.07 × 10 4 [0.60 × 10 4 –4.45 × 10 4 ] CFU/g, respectively; p  < 0.01), and severer histological inflammation ( p  < 0.001) than the control group. The Aquacel Ag group was only able to show significantly better wound healing than the infection group ( p  < 0.001). The new incisional SSI model exhibited all clinical manifestations of incisional SSI. It could be utilized to assess the effectiveness of newly developed treatments for incisional SSI.